Optimal design of traffic calming devices using computer simulation. (2nd September 2020) - Khorshid, Emad; Awada, Habib; Falah, Abdulazim H; Elkholy, Ahmed
ABSTRACT: Speed control humps and dips are the most effective and widely used devices, to control vehicle speeds in urban areas. Their geometry varies from type to type based on the criteria used. This study aims at developing new designs for speed hump and dip using commercially available simulation and optimization software. The numerical simulation for vehicle-hump dynamics was developed using ADAMS software and then is linked to MATLAB software to determine speed hump/dip optimum designs that provide discomfort feeling to the driver if vehicle speed exceeds the specified limit, and tolerable comfort if speed is less than or equal the specified limit. The acceptable range of vibrations and shocks exposure resulted from passing over the humps or dips are based on British BS6841:1987 and ISO2631-5:2004 standards. These standards address human health and comfort level in terms of the acceptable range of whole body vibration exposure. The study shows that, for speed limits lower than 10 km/h and higher than 45 km/h, the optimal humps are more efficient than dips. On the other hand, the study shows that for midrange speed limits between 10 and 45 km/h, the optimal dips were superior over optimal humps.